Visceral adipose tissue glucose uptake is linked to prognosis in multiple myeloma patients: An exploratory study. Issue 6 (June 2021) - da Cunha Júnior, Ademar Dantas; Silveira, Marina Nogueira; Takahashi, Maria Emilia Seren; de Souza, Edna Marina; Mosci, Camila; Ramos, Celso Dario; Brambilla, Sandra Regina; Pericole, Fernando Vieira; Prado, Carla M.; Mendes, Maria Carolina Santos; Carvalheira, José Barreto Campello
Summary: Background & aims: The use of computerized tomography to opportunistically assess body composition has highlighted abnormalities such as low muscle mass and high adiposity may be hidden conditions in cancer patients. However, the role of skeletal muscle (SM), subcutaneous (SAT) and visceral (VAT) adipose tissue glucose uptake measured by 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET)-CT on patient prognostication is unclear. Methods: Patients with multiple myeloma (MM) with satisfactory image frame for assessing body composition and for semi-quantification of SM, SAT and VAT glucose uptakes were included. Plasmatic pro-inflammatory cytokine and adipokine levels were measured. Results: High VAT mean standardized uptake value (SUV) at baseline was associated with shorter event-free survival (EFS) (hazard ratio [HR]: 7.89; 95% confidence interval [CI], 1.58–39.30; P = 0.012) and overall survival (OS) (HR, 15.24; 95% CI, 2.69–86.30; P = 0.002) among patients with newly diagnosed MM, even after adjustment for covariates. The highest tertile of VAT SUV was significantly correlated with worse MM-EFS (HR for the highest vs the lowest tertile 3.71; 95% CI, 1.22–10.56; Ptrend = 0.035) and mortality (HR, 4.41; 95% CI, 1.28–12.77; Ptrend = 0.019). Notably, patients with higher VAT SUV presented with lower VAT area, VAT index, higher SAT SUV, and higher number of individuals with visceral obesity (all P < 0.01). Additionally, we found a negative correlation between VAT mean SUV with leptin (R 2 = 0.20, P = 0.003); no correlations were detected between VAT mean SUV and resistin, tumor necrosis factor (TNF) or interleukin (IL)-6. Conclusions: Functional VAT activity estimated by 18 F-FDG PET-CT is a relevant prognostic factor in MM patients, specifically, a higher VAT SUV might be an early biomarker of cancer cachexia in these patients.